VICTIM-CENTERED JUSTICE APPROACH IN HANDLING DOMESTIC VIOLENCE FROM THE PERSPECTIVE OF MOI PAPUA CUSTOMARY LAW - Tri Wulandari; Ursula Temongmere (Papua Law Review, 2026)
Domestic violence (DV) remains one of the most persistent forms of gender-based violence in Indonesia, including among Indigenous communities in Papua, where customary law continues to play a significant role in regulating social relations and resolving family disputes. Within the Moi Indigenous community, domestic violence cases are frequently addressed through customary mechanisms emphasizing reconciliation, restoration of family harmony, and customary compensation rather than formal criminal proceedings. While these practices contribute to maintaining social cohesion and preserving Indigenous values, they may not adequately safeguard victims' rights, participation, safety, and long-term recovery. This study aims to examine the implementation of a victim-centered justice approach in handling domestic violence from the perspective of Moi Papua customary law and to explore its compatibility with Indonesia's legal framework, particularly Law Number 23 of 2004 concerning the Elimination of Domestic Violence. This research employs a normative juridical method using statutory, conceptual, and customary law approaches, supported by relevant legal literature and secondary data. The findings reveal that the customary justice system of the Moi community prioritizes communal harmony and dispute resolution but provides limited attention to victims' psychological recovery, legal protection, restitution, and active participation in decision-making. Consequently, victims may experience secondary victimization when their interests are subordinated to collective reconciliation. The study argues that integrating victim-centered justice principles into the customary justice system can strengthen victim protection without undermining the cultural identity and legal traditions of the Moi community. It recommends strengthening collaboration between customary leaders, law enforcement agencies, and victim support institutions to establish culturally responsive legal mechanisms that balance Indigenous customary values with human rights principles and comprehensive protection for victims of domestic violence